2021
DOI: 10.1108/idd-03-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Library leadership in Nigeria and COVID-19 pandemic

Abstract: Purpose The current scourge of COVID-19 in educational enterprise requires that libraries tame the wave of the pandemic through effective leadership. This paper aims to investigate library leadership in Nigeria and COVID-19 pandemic. Design/methodology/approach Descriptive research design was used for the study. A structured questionnaire designed with Google Form and administered online was used to elicit data from 137 heads of academic and public libraries and their deputies in South West, Nigeria. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…From the challenges mentioned; the international students felt the following recommendations should be addressed; the need to have access to more online resources, especially, journals that were requiring payment; the need to have an organized library orientation, so that they can have attachment with their university and staff; the need to have more staff in the university who are able to speak in the English language; the need to have continuous user education due to the diversification of the information available in the university portal, it was felt that the user education should be treated as a mandatory course for the international students. Arapasopo and Adekoya (2021) observe that though COVID-19 has affected the operations of libraries, libraries need to make amendments to their operations, so as to serve their users adequately. Some students felt the need to have librarians attached to their schools/faculty, so that they can be readily available to assist when need be.…”
Section: Discussionmentioning
confidence: 99%
“…From the challenges mentioned; the international students felt the following recommendations should be addressed; the need to have access to more online resources, especially, journals that were requiring payment; the need to have an organized library orientation, so that they can have attachment with their university and staff; the need to have more staff in the university who are able to speak in the English language; the need to have continuous user education due to the diversification of the information available in the university portal, it was felt that the user education should be treated as a mandatory course for the international students. Arapasopo and Adekoya (2021) observe that though COVID-19 has affected the operations of libraries, libraries need to make amendments to their operations, so as to serve their users adequately. Some students felt the need to have librarians attached to their schools/faculty, so that they can be readily available to assist when need be.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that the transactional leadership style can be effective against crisis. Yet, with a few notable exceptions, e.g., in coordinating the United States' national response to the COVID-19 pandemic ( Bergquist, Otten, & Sarich, 2020 ) and in steering Nigerian Libraries to survive the pandemic ( Arapasopo & Adekoya, 2021 ), research examining the effectiveness of transactional leadership in piloting organizations through the pandemic is still lacking. We view this as a significant omission in the theoretical development of marketing literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Arapasopo and Adekoya (2021) investigated the viewpoints of 137 academic library executives in Nigeria and concluded that libraries could effectively manage the COVID-19 waves. According to their findings, transformational and transactional leadership styles were more productive in managing libraries than laissez-faire attitudes, and library executives with effective leadership styles would be successful in the face of the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%